Quinolizidine and pyrrolizidine alkaloid chemical ecology: a mini-review on their similarities and differences - Wink, Michael (Journal of chemical ecology, 2019)
This mini-review summarizes over 40 years of research on quinolizidine (QAs) and pyrrolizidine alkaloids (PAs). Emphasis is on the chemical ecology of both groups of alkaloids, which serve as general defense compounds against herbivores for the plants producing them. For QAs and PAs, a number of insects (aphids, moths, beetles) have acquired tolerance. These specialists store the alkaloids and use them as defense chemicals against predators. In some PA sequestering moths, the adaptation is even more intricate and advanced. PAs can function as a morphogen to induce the formation of male coremata, inflatable organs that dissipate pheromones. In these insects, PAs are additionally used as a precursor for male pheromones. Female moths utilize their own PAs and those obtained from males via the spermatophore as nuptial gift, to transfer them to the eggs that thus become chemically protected. Novel genomic technologies will allow deeper insights in the molecular evolution of these two classes of alkaloids in plant-insect interactions.
Gesehen am 27.05.2019
Published online: 6 August 2018